Penegakan Hukum Terhadap Kekerasan Seksual Secara Non Fisik Oleh Tenaga Pendidik Perguruan Tinggi - Matauseja, Siloam Putrisia; Sopacua, Margie Margie Gladis; Fadillah, Astuti Nur (PATTIMURA Law Study Review, 2025)
Various cases of sexual violence in higher education environments have recently occurred, leading to the enactment of Law Number 12 of 2022 on Sexual Violence Crimes and Regulation of the Ministry of Education, Culture, Research, and Technology Number 55 of 2024 on the Prevention and Handling of Violence in Higher Education, which serve as specific regulations for addressing sexual violence crimes, law enforcement, and sanctions. This is exemplified by an incident at Pattimura University, where a lecturer from the Faculty of Teacher Training and Education of PPKn committed verbal sexual violence against one of his students on March 2, 2024. The research method used is empirical juridical research conducted through legislative and field approaches. The sources of legal materials used include primary, secondary, and tertiary legal materials, and the technique for analyzing legal materials used is qualitative. Research shows that the causes of sexual violence in higher education institutions are power relations, psychological factors, cultural and social aspects, and the role of the victim. More specifically, verbal sexual violence by educators in higher education occurs due to patriarchal ideology, stigma, gender stereotypes, and sexism, a culture of victim blaming, and the lack of clear legal frameworks prior to Permendikbud Ristek PPKS, UU TPKS, and Permendikbud Ristek PPKPT. Verbal sexual violence by educators in higher education certainly requires strict law enforcement. Law enforcement against verbal sexual violence in higher education is initially carried out by the institutions through the Task Force for the Prevention and Handling of Violence in Higher Education, involving stages of reporting, follow-up on reports, investigations, preparation of conclusions and recommendations, and follow-up on conclusions and recommendations.